2022
DOI: 10.1111/mpp.13237
|View full text |Cite
|
Sign up to set email alerts
|

The secreted ribonuclease T2 protein FoRnt2 contributes to Fusarium oxysporum virulence

Abstract: Secreted RNase proteins have been reported from only a few pathogens, and relatively little is known about their biological functions. Fusarium oxysporum is a soilborne fungal pathogen that causes Fusarium wilt, one of the most important diseases on tomato. During the infection of F. oxysporum , some proteins are secreted that modulate host plant immunity and promote pathogen invasion. In this study, we identify an RNase, FoRnt2, from the F. oxysporum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…VdEG1 is another GH12 protein secreted by Verticillium dahliae and it plays an important role in virulence ( Gui et al, 2017 ). In addition, FoRnt2, a secreted ribonuclease T2 protein, contributes to the full virulence of F. oxysporum in tomato plants via its RNase activity ( Qian et al, 2022 ). Moreover, by targeting the host cell nucleus, the secreted Vd424Y protein from V. dahliae , a glycoside hydrolase family 11 protein, is required for full virulence ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…VdEG1 is another GH12 protein secreted by Verticillium dahliae and it plays an important role in virulence ( Gui et al, 2017 ). In addition, FoRnt2, a secreted ribonuclease T2 protein, contributes to the full virulence of F. oxysporum in tomato plants via its RNase activity ( Qian et al, 2022 ). Moreover, by targeting the host cell nucleus, the secreted Vd424Y protein from V. dahliae , a glycoside hydrolase family 11 protein, is required for full virulence ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…brongniartii, Cordyceps sp , Akanthomyces lecanii, Trichoderma sp., and Metarhizium sp , possess both BbRNT2 and BbTrv homologs. Yeast RNY1, plant fungal pathogens Fusarium oxysporum FoRnt2 and Ustilago maydis Nuc1 and Nuc2 were classified into the BbTrv clade, whereas a member of Colletotrichum viniferum was classified into the BbRNT2 clade (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…These effects may be due to their enzyme function in utilization of the extracellular RNA (presenting in maize apoplast) as a phosphate source at least . A secretory RNase T2, FoRnt2, of Fusarium oxysporum, is localized in both the cytoplasm and nucleus of plant cells and contributes to fungal virulence possibly through the degradation of host RNA …”
Section: Introductionmentioning
confidence: 99%
“…We previously performed a secretome-wide analysis in Fol to provide new sight of infection-related proteins and found that most of them with an N-terminal SP were annotated as enzymes ( Li J. et al, 2020 ). To date, three secreted proteins are shown to contribute virulence, and two of them encode the ribonuclease and peptidase, respectively ( Li et al, 2022 ; Qian et al, 2022a , b ). In this study, we characterized one aspartic protease FolAsp from the Fol secretome.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the FolSvp1 is characterized to contribute virulence by translocating a key defense protein PR1 to dampen the host defense ( Li et al, 2022 ). FoRnt2, a secreted ribonuclease T2 protein, contributes to the full virulence of F. oxysporum in tomato plants depending on its RNase activity ( Qian et al, 2022a ). The FoAYP1 contributes to the virulence of Fol through peptidase activity on host protein ( Qian et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%